The impact of transliterative Deductive Method (Hud-Hud) and the native Arabic speakers on the foreign speakers: a pilot study - Ahmad Saad, Fathinul Fikri; Fahmy Ahmed, Omar Ahmed (Scientific Research Support Fund at the Ministry of Higher Education and the Deanship of Academic Research, Mutah University, Karak, Jordan, 2022)
There are few studies on the influence of the native Arabic speakers in enhancing the understanding among subjects residing in non-Arabic speaking language utilizing the deductive method in mediating teaching. The study aimed at evaluating the influence of the native speaker on the effectiveness of the “Hud-Hud” deductive teaching style among the non-Arabic speaking in Malaysia. The study was conducted on a selected group of urbanized Malaysians subjects (n=30), who were dichotomized into the control group (n=15) and the test group (n=15). All subjects underwent a-60-hour elementary Arabic teaching programme utilizing the "Hud-Hud –deductive" method taught by a local (Malay) speaker. Two Arabic native speakers had provided additional teaching guide to the test group before a series of test performances were conducted. The results showed that the younger age subjects (age < 40 years) had a significantly higher score than the elder age group (mean; 2.04±0.404 vs. 1.59±0.97; p<0.05). The test group subjects had significantly higher rubricscores than the control group (mean; 0.62±0.16 vs. 0.59± 0.50; p<0.05). Moreover, there was significantly higher rubric score achieved among subjects who had previous Arabic teaching exposure (mean; 2.04±0.404 vs. 1.59±0.97; p<0.05). The native speakers are the potential predictive marker in ensuring the effectiveness of the deductive “Hud-Hud" teaching for the foreign in the non-Arabic speaking country.